Pengaruh Suplementasi Tepung Terigu terhadap Pertumbuhan dan Laju Pengasaman Probiotik Lactobacillus acidophilus - Elmy Mariana; Hilda Susanti (Jurnal Teknologi dan Industri Pertanian Indonesia, 2012)
This study aimed to determine the effect of the addition of wheat flour as a potential prebiotic on growth and acidification rate of probiotic Lactobacillus acidophilus (L. acidophilus) in fermented milk. The study was conducted by adding the flour with concentrations 1, 3 and 5% in the fermentation medium with 15% skim milk. Observed growth parameters including the total number of probiotic bacteria, decreasing pH and increasing acidity during the fermentation process. The results showed that the addition of wheat flour speed up the fermentation time, accelerate the process of decline in pH, increasing the acidity and increase the total number of probiotic bacteria.This study shows that wheat flour supplemented in fermented milk could enhance the growth characteristics of probiotics L. acidophilus. Keywords: probiotics, L. acidophilus, growth, wheat flour